Space/place matters - Milani, Tommaso M.; Williams, Quentin; Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
This special issue of Multilingual Margins on the theme of â€œSpace/place mattersâ€ has its origin in a doctoral summer school organised in December 2016 by the Department of Linguistics and the Centre for Multilingualism and Diversities Research at the University of the Western Cape as part of a collaboration with the University of Oslo and three other South African universities â€“ Stellenbosch University, University of Cape Town and University of the Witwatersrand â€“ and financed by Research Council of Norwayâ€™s programme International Partnerships for Excellent Education, Research and Innovation (INTPART). Doctoral students based in Norway and South Africa attended the summer school, presented their research projects, and were encouraged to submit an article to Multilingual Margins. This was with a view to training budding scholars to deal with the peer-review process of academic publishing. This special issue is the material outcome of this process and includes three articles that have a common interest in unpicking the complex relationship between language and space/place.